2021
DOI: 10.1007/s11920-021-01262-8
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Outcomes of Unaccompanied Refugee Minors: a Rapid Review of Recent Research

Abstract: Purpose To examine mental health outcomes of unaccompanied refugee minors during global policy shift. Additionally, to consider mental health service delivery and placement type for this group. Methods A rapid systematic search of research published since 2018 which related to mental health outcomes of unaccompanied refugee minors. Data extracted, risk of bias assessed and outcomes reviewed qualitatively. Research Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 51 publications
1
18
0
2
Order By: Relevance
“…Other protective factors involved receiving social support and having contact with family members (H€ ohne et al 2020). In a review of mental health outcomes of young unaccompanied refugees, Bamford et al (2021) came to similar conclusions as they identified lack of social support, poor language skills, and experiences of discrimination and daily hassles as important predictors of outcomes.…”
Section: Introductionmentioning
confidence: 80%
“…Other protective factors involved receiving social support and having contact with family members (H€ ohne et al 2020). In a review of mental health outcomes of young unaccompanied refugees, Bamford et al (2021) came to similar conclusions as they identified lack of social support, poor language skills, and experiences of discrimination and daily hassles as important predictors of outcomes.…”
Section: Introductionmentioning
confidence: 80%
“…Alto et al state that nurturing UMs’ foster family environments is central, as enduring conflicts can exacerbate adolescents’ symptoms [ 32 ]. The type of placement may also influence UM’s prognosis [ 33 ]. Living in foster care is sometimes a protective factor, possibly due to higher level of social support, safety and stability within this setting [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Müller et al (2019), 64% of UMs seeking asylum were found to meet the diagnostic criteria for Post-Traumatic Stress Disorder (PTSD); when left untreated, PTSD can lead to serious behavioral problems in children (Brymer et al, 2019). Furthering these challenges for UMs are factors such as limited social support, poor language fluency, limited resources, discrimination, daily hassles, and asylum status which have been linked to more emotional problems (Bamford et al, 2021).…”
Section: Introductionmentioning
confidence: 99%